As dificuldades de comunicação argumentativas em fóruns de discussão online com finalidade pedagógica - Silva, Liliane Pereira da (2010)
The aim of this research was to verify how argumentation occurs in an online educational forum as well as to map the interaction network in the analyzed forum, observing how the discussion was set up in it. The research was held with a group of Práticas de Leitura e Escrita na Contemporaneidade, offered by Secretariat for Education of São Paulo (SEE-SP) in association with Pontifical Catholic University of São Paulo (PUC-SP) in the Post-graduation Program of Applied Linguistics and Language Studies (LAEL). The course was exclusively online and attended by aproximately 10,000 teachers of all disciplines of Basic Education II, teacher-coordinators (PCs), teacher-coordinators and teaching supervisors of the state schools in São Paulo. The theoretical basis that guided the research was divided into three aspects: the first one related to interaction, according to Gunawardena, Lowe and Anderson (1997) and Anderson and Kanuka (1998); the second one related to language analysis in a real context of use, guided by Systemic Functional Linguistics, more precisely by the concept of Contextual Configuration (CC) and generic structure potential (GSP) developed by Halliday e Hasan (1989); and the third one related to argumentation in discussion forums according to the studies of Coffin, Painter and Hewings (2005). Based on the qualitative analysis of the discussion forum, it was possible to verify how interaction and argumentation can relate in the environment. As the interaction develops better, the possibilities of deepening the discussion increase, and, consequently, the chances of developing more argumentative strategies increase too. It was also possible to realize how the articulation between the interaction development and discussion is like in relation to the type of mediation that occurred in the analyzed environment